Beyond the wall : Germany's road to unification - Pond, Elizabeth (A Twentieth Century Fund book, 1993)
Beyond the Wall is the first book, in either English or German, to tell the whole story of the extraordinary revolution that demolished the Berlin Wall, ended the cold war, and tore apart the Soviet empire. Elizabeth Pond, former Moscow and European correspondent for the Christian Science Monitor, was an eyewitness to the dramatic events of 1989-92 and to the fifteen years of relations between Germany and Eastern Europe leading up to them. Pond weaves together in riveting prose the strands of events that are usually recounted separately. Rather than looking just at the East German revolt or the process of unification that created a new nation, she traces the interaction of these events and their diplomatic consequences for Europe. Pond shows the political, economic, and social forces at work - leading up to the unification, during the transition process, and in the aftermath. Looking at the European framework, she explains how significantly the European Community and its move toward integration both affected and were affected by German unification. The book contains a wealth of new information from hundreds of interviews with top German and American policymakers, East German Politburo members, and average German citizens. It also incorporates up-to-date research on such topics as the Stasi secret police and the midlife crisis of the German left. Pond concludes with an assessment of the roles of the United States and a united Germany in the new Europe. Calling for a continued partnership between the United States and Germany, who "have come through a common baptism of fire since the fall of the Berlin Wall," Pond casts an optimistic eye toward the future.